Dephasing enhanced transport in non-equilibrium strongly-correlated quantum systems - Mendoza-Arenas, J; Grujic, T; Jaksch, D; Clark, SR (2013)
A key insight from recent studies is that noise, such as dephasing, can improve the efficiency of quantum transport by suppressing coherent single-particle interference effects. However, it is not yet clear whether dephasing can enhance transport in an interacting many-body system. Here we address this question by analysing the transport properties of a boundary driven spinless fermion chain with nearest-neighbour interactions subject to bulk dephasing. The many-body non-equilibrium stationary state is determined using large scale matrix product simulations of the corresponding quantum master equation. We find dephasing enhanced transport only in the strongly interacting regime, where it is shown to induce incoherent transitions bridging the gap between bound dark-states and bands of mobile eigenstates. The generic nature of the effect is illustrated and shown not to depend on the integrability of the model considered. As a result dephasing enhanced transport is expected to persist in more realistic driven systems of strongly-correlated particles.